DAMPAK PENGGUNAAN OBAT BERPOTENSI HEPATOTOKSIK TERHADAP LUARAN KLINIS PADA PASIEN SIROSIS HATI - Ariesta Kirana Efmisa; Devahimer Harsep Rosi; Rido Farnandi; Azimatur Rahmi; Deswati Deswati; Khairil Armal (LPPM Universitas Abdurrab, 2024)
Liver cirrhosis is a pathological liver disease characterized by the formation of fibrous tissue and regenerative nodules in liver cells. The potential for hepatotoxicity due to the use of hepatotoxic drugs leads to worsening of the liver disease suffered by these patients. This study aims to assess the impact of using potentially hepatotoxic drugs on patients' clinical outcomes. This study was an observational study with a cross-sectional design. Data were collected retrospectively through the medical records of patients with liver cirrhosis hospitalized in 2021. The clinical outcomes studied were SGOT, SGPT, albumin, total bilirubin and length of hospitalization. The results obtained were tested using the Kruskal-Wallis statistical test. A total of 62 patients with liver cirrhosis met the inclusion criteria as the study sample. The number of potentially hepatotoxic drug prescriptions received by patients based on Likelihood scores with categories A, B, C, D and E was 368 drugs out of 776 total drug prescriptions (47.4%). The most commonly prescribed potentially hepatotoxic drugs were paracetamol, ceftriaxon, and levofloxacin. It can be concluded that potentially hepatotoxic drugs are still prescribed to patients with liver cirrhosis. Age, gender, child pugh-score, number of drugs, and number of potentially hepatotoxic drugs had no significant effect (p>0.1) on SGOT, SGPT, albumin and total bilirubin. However, patients who received more drugs would have a higher.